2002
DOI: 10.1007/s00125-002-0831-8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of 8-oxo-7, 8-dihydro-2′-deoxyguanosine as a predictor of the development of diabetic nephropathy

Abstract: Aims/hypothesis. The increased oxidative stress in diabetes is known to contribute to the progression of diabetes and its complications. We have reported a significant relation between the content of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG), a product of oxidative DNA damage in urine or leukocytes and the severity of diabetic nephropathy and retinopathy [1]. We investigated whether 8-oxodG in urine or leukocytes is associated with the progression of diabetic nephropathy. Methods. We measured urinary 8-oxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 22 publications
5
107
0
3
Order By: Relevance
“…25 Additional studies have shown that urinary 8-OHdG correlated with the severity of DN and retinopathy 27 and also with future development of DN. 28 Others 29 have shown that in streptozotocin-induced diabetic rats, measurement of levels of 8-OHdG from mitochondrial DNA was higher in both renal cortices and papillae and so were the urinary 8-OHdG levels. In contrast, the levels of 8-OHdG in nuclear DNA were not elevated.…”
Section: Discussionmentioning
confidence: 99%
“…25 Additional studies have shown that urinary 8-OHdG correlated with the severity of DN and retinopathy 27 and also with future development of DN. 28 Others 29 have shown that in streptozotocin-induced diabetic rats, measurement of levels of 8-OHdG from mitochondrial DNA was higher in both renal cortices and papillae and so were the urinary 8-OHdG levels. In contrast, the levels of 8-OHdG in nuclear DNA were not elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated urinary levels of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), a marker of oxidative stress, predict the progression of diabetic nephropathy in patients with T2D [47]. Patients with T1D or T2D and with higher levels of proinflammatory cytokines and chemokines (interleukin 6, interleukin 18, and monocyte chemoattractant protein-1), high-sensitivity Creactive protein (hsCRP, a marker of subclinical inflammation), or adhesion molecules (soluble vascular cellular adhesion molecule-1 and soluble Eselectin) are at higher risk for developing nephropathy and for advancing to more severe kidney disease [48][49][50][51].…”
Section: New Risk Factors For Diabetic Nephropathymentioning
confidence: 99%
“…70,71 Furthermore, in a prospective study, it was demonstrated that in type 2 diabetic patients, higher levels of urinary 8-OHdG were associated with the progression of diabetic nephropathy. 72 A recent study demonstrated that low doses of erythropoietin inhibit oxidative stress and early vascular changes in the experimental diabetic retina. 73 The investigators of this study have concluded that erythropoietin may prevent microvascular damage in the diabetic retina.…”
Section: Contribution Of Inflammation and Oxidative Stress To Dr And mentioning
confidence: 99%